Non-Enveloped Virus Entry: Structural Determinants and Mechanism of Functioning of a Viral Lytic Peptide. Issue 17 (28th August 2016) - Bajaj, Saumya; Dey, Debajit; Bhukar, Rohan; Kumar, Mohit; Banerjee, Manidipa
Abstract: In the absence of lipid envelopes and associated fusion proteins, non-enveloped viruses employ membrane lytic peptides to breach the limiting membranes of host cells. Although several of these lytic peptides have been identified and characterized, their manner of deployment and interaction with host membranes remains unclear in most cases. We are using the gamma peptide of Flock House Virus (FHV), a model non-enveloped virus, to understand the mechanistic details of non-enveloped virus interaction with host cell membranes. We utilized a combination of biophysical assays, molecular dynamics simulation studies, and single-particle cryo-electron microscopy to elucidate the functional and structural determinants for membrane penetration by gamma in context of the FHV capsid. Although the amphipathic, helical N-terminal region of gamma (γ1) was previously thought to be the membrane-penetrating module, with the C-terminal region having a supporting role in correct structural positioning of γ1, we demonstrate that the C terminus of gamma directly participates in membrane penetration. Our studies suggest that full-length gamma, including the hydrophobic C terminus, forms an alpha-helical hairpin motif, and any disruption in this motif drastically reduces its functionality, in spite of the correct positioning of amphipathic γ1 in the virus capsid. Taken together, our data suggest that the most effective module for membrane disruption is a pentameric unit of full-length gamma, released from the virus, which associates with membranes via both N- and C-terminal ends. Graphical Abstract: Highlights: Combinatorial study of biochemical assays, cryo-electron microscopy, and molecular dynamics simulations. The alpha-helical hairpin motif in the gamma peptide of Flock House Virus was disrupted. This causes loss of membrane penetration functionality, while structural positioning is unaffected. MD simulation shows membrane disruption facilitated by pentameric unit of full-length gamma.